Serum zinc, copper and cobalt level in normal cyclic, anoestrus and repeat breeder buffaloes - SINGH, BHOOPENDRA; RAWAL, C V S; SINGH, J P (The Indian Journal of Animal Reproduction, 2023)
In the present study, serum concentration of trace minerals was estimated in normal cyclic, anoestrus and repeat breeder buffaloes. The serum level of Zn was lower in an oestrus (0. 72±0.05μg/ml) and repeat breeder buffaloes (0.88±0. I 5μg/ml) as compared to normal cyclic buffaloes (I .00±0.04μg/ml). However, the difference was not significant. The serum level of Cu was significantly (P<0.05) lower in anoestrus (0.59±0.03μg/ml) and repeat breeder buffaloes (0.62±0.03μg/ml) as compared to normal cyclic buffaloes (0.88±0.03μg/ml). The serum level of Co was non-significantly lower in anoestrus (0.018±0.00Iμg/ml) and repeat breeder buffaloes (0.016±0.00 I μg/ml) as compared to normal cyclic buffaloes (0.022±0.002μg/ml).